BALAI REHABILITASI SOSIAL BAGI DISABILITAS FISIK (TUNA NETRA, TUNA RUNGU WICARA, DAN TUNA DAKSA) DI SURAKARTA - Rifani Lutfia Kusumaputri; Wiwik Setyaningih; Ummul Mustaqimah (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Social rehabilitation center for physical disability (blind, hearing and speech impaired, and physically disabled) in Surakarta is a coaching spot that provide basic services, psychosocial rehabilitation services, health rehabilitation services, provision of additional knowledge and skills, and change behavior rehabilitation services in Surakarta. Disability means people who have limited or different abilities. The goal of the social rehabilitation center that is intended for people who have the physical disorder or limitations (disability) that are sight, hearing, speech and body through character approach interaction with disability coequal or the physical environment. The goal is to create a physical place as a place of rehabilitation and counseling for physical disability that is blind, hearing and speech impaired, and physically disabled to live independently by providing infrastructure facilities appropriate accessibility standards (safe, easy, and convenient) for them and give place socialization/interaction place with physical disabilities as well socialization place between physical disability with the community so that they can co-existence with as provision of independent living in the community through a behavioral approach in architecture. Key words: Social rehabilitation center, physical disability, accessibility